Global burden of metabolic disorders among women of child-bearing age, 1990–2021: a population-based study - Junyu Chen; Dihan Fu; Tianqi Ma; Minghong Chen; Xuerui Wang; Jun Yi (BMC Women's Health)
Abstract Background Metabolic disorders have a significant impact on the health of women of childbearing age (WCBA) but remain underemphasized. This study aims to assess the global, regional, and national burden of metabolic disorders in WCBA from 1990 to 2021. Methods Prevalence, mortality, and disability-adjusted life years (DALYs) related to metabolic disorders in WCBA from 1990 to 2021 were obtained from the Global Burden of Disease (GBD) 2021. Annual percentage changes were calculated, and stratified analyses were conducted based on age, region, nation, and socio-demographic index levels to assess the distribution of metabolic disorders in WCBA. Results Globally, the overall burden of metabolic disorders among WCBA has increased. In 2021, obesity (330.21 [148.37-518.36]) had the highest age-standardized DALYs rate, followed by hypertension (200.75 [154.67-245.47]), type 2 diabetes mellitus (175.11 [134.18-223.42]), hyperlipidemia (139.02 [101.32-173.61]), and non-alcoholic fatty liver disease (10.1 [7.17-13.92]). The most significant changes of the overall metabolic disorders burden in WCBA were observed in younger age groups. The burden of metabolic disorders was higher in less-developed regions. Conclusions Given the marked increase in the burden of metabolic disorders among younger WCBA, it is recommended that healthcare management be reinforced for this demographic. Furthermore, based on the varying burdens observed across regions, targeted metabolic interventions for WCBA should be tailored to local conditions.